Tilapia wastes to valuable materials: A brief review of biomedical, wastewater treatment, and biofuel applications. (2022) - Lee, T.C.; Mohd Pu'ad, N.A.S.; Alipal, J.; Muhamad, M.S.; Basri, H.; Idris, M.I.; Abdullah, H.Z.
Abstract: Scale, skin, internal organs, viscera, trimmings, bone, tails, and fins are common fish wastes that are difficult to dispose of. Discarded fish wastes have become a global environmental concern. The conversion of fish waste into valuable materials, on the other hand, is currently in high demand around the world. In over 120 countries, there are numerous tilapia species available on the market. However, because of its low commercial value, tilapia wastes are discarded. This brief review summarises recent works on tilapia wastes utilisation in three areas: biomedical applications such as wound dressing treatment, synthesis of hydroxyapatite and gelatin extraction, wastewater treatment, and biofuel. The recovery of valuable materials from tilapia biowaste helps to reduce the environmental problems caused by discarded tilapia wastes.